Sustainability initiatives in urban freight transportation in Europe - Krisztián J. Galambos; Alexa B. Palomino-Hernández; Vera C. Hemmelmayr; Belma Turan (Transportation Research Interdisciplinary Perspectives, 2024)
The number of people living in cities worldwide is rising and hence also the number of goods that have to be transported in cities. Accordingly cities seek to employ sustainability initiatives to mitigate the negative effects of (freight) transportation such as traffic jams, emissions and noise. This paper collects different sustainability initiatives implemented in Europe in the last ten years. It analyzes the projects, provides a classification and derives lessons learned. That way recommendations to city planners can be formulated.